A new method for the assessment of patient safety competencies during a medical school clerkship using an objective structured clinical examination - Renata Mahfuz Daud-Gallotti; Christian Valle Morinaga; Marcelo Arlindo-Rodrigues; Irineu Tadeu Velasco; Milton Arruda Martins; Iolanda Calvo Tiberio (Clinics, 2011)
INTRODUCTION: Patient safety is seldom assessed using objective evaluations during undergraduate medical education. OBJECTIVE: To evaluate the performance of fifth-year medical students using an objective structured clinical examination focused on patient safety after implementation of an interactive program based on adverse events recognition and disclosure. METHODS: In 2007, a patient safety program was implemented in the internal medicine clerkship of our hospital. The program focused on human error theory, epidemiology of incidents, adverse events, and disclosure. Upon completion of the program, students completed an objective structured clinical examination with five stations and standardized patients. One station focused on patient safety issues, including medical error recognition/disclosure, the patient-physician relationship and humanism issues. A standardized checklist was completed by each standardized patient to assess the performance of each student. The student's global performance at each station and performance in the domains of medical error, the patient-physician relationship and humanism were determined. The correlations between the student performances in these three domains were calculated. RESULTS: A total of 95 students participated in the objective structured clinical examination. The mean global score at the patient safety station was 87.59 ± 1.24 points. Students' performance in the medical error domain was significantly lower than their performance on patient-physician relationship and humanistic issues. Less than 60% of students (n = 54) offered the simulated patient an apology after a medical error occurred. A significant correlation was found between scores obtained in the medical error domains and scores related to both the patient-physician relationship and humanistic domains. CONCLUSIONS: An objective structured clinical examination is a useful tool to evaluate patient safety competencies during the medical student clerkship.